Pengaruh pH Sabun Cair Virgin Coconut Oil (VCO) Terhadap Aktivitas Antibakteri Staphylococcus aureus - Wijaya, Mariska Aurelia; Cahyanti, Naomi Dwi (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2025)
Virgin coconut oil contains fatty acids that function as skin softeners and antibacterials. In general, soaps have an alkaline pH which causes the skin to feel dry. Neutral pH soap will be more acceptable to the skin , but is a suitable pH for bacterial growth. The purpose of this study was to determine the antibacterial activity of Virgin Coconut Oil soap with alkaline and neutral pH against Staphylococcus aureus. The materials used were Virgin Coconut oil, KOH, propylene glycol, glycerin, Coco DEA, hydroxypropyl methylcellulose, and citric acid. The research method used a posttest-only control group design with descriptive-quantitative data analysis. Tests were carried out by making 2 soap samples with alkaline and neutral pH, then evaluated organoleptically, pH, viscosity, specific gravity, foam height, and antibacterial activity. The results of the organoleptical evaluation of both soap samples are liquid texture, gray in color, with a vanilla aroma. The pH value of alkaline soap is 8.42 and the pH of neutral soap is 7.09. The viscosity, specific gravity, and foam height values of alkaline pH soap and neutral pH soap have met the criteria for liquid soap requirements. Both soap samples have Staphylococcus aureus antibacterial activity based on the inhibition zone formed. Statistical analysis with the Mann Whitney test showed that there was a significant difference in antibacterial activity in alkaline and neutral pH soaps, with greater inhibition in alkaline pH soap than in neutral pH.